Does investment really drive local economic growth? Evidence from a non-metropolitan Indonesian city - Mira Hastin; Erni Febrina Harahap; Kasman Karimi (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Investment is widely recognized as a key driver of economic growth because it expands productive capacity and stimulates structural transformation. However, most empirical studies on the investment–growth relationship focus on national or provincial scales, while city-level dynamics in non-metropolitan areas remain relatively underexplored. This gap limits the understanding of how capital formation operates within smaller regional economies characterized by different institutional capacities and sectoral structures. Aims: This study aims to examine the influence of investment on regional economic growth in Sungai Penuh City, Indonesia, during the 2020–2024 period. Methods: The research employs a quantitative explanatory approach using secondary time-series data obtained from the Central Bureau of Statistics. Economic growth is measured using Gross Regional Domestic Product (GRDP) at constant prices, while investment is represented by Gross Fixed Capital Formation (GFCF). The relationship between variables is estimated using a log-linear regression model with the Ordinary Least Squares (OLS) method to identify investment elasticity in regional output. Result: The estimation results indicate that investment has a positive and statistically significant effect on regional economic growth. The elasticity coefficient of 0.967 implies that a 1 percent increase in investment is associated with an approximate 0.97 percent rise in regional output. The coefficient of determination (R² = 0.972) shows that investment explains a substantial proportion of the variation in economic growth during the study period. Conclusion: These findings highlight the critical role of capital formation in strengthening economic performance in non-metropolitan regions. The strong elasticity between investment and output underscores the importance of productive capital accumulation in supporting sustainable regional development and evidence-based economic policy formulation.